Dissociable effects of oxycodone on behavior, calcium transient activity, and excitability of dorsolateral striatal neurons - Barry, Joshua; Oikonomou, Katerina D.; Peng, Allison; Yu, Daniel; Yang, Chenyi; Golshani, Peyman; Evans, Christopher J.; Levine, Michael S.; Cepeda, Carlos (Frontiers in Neural Circuits, 2022)
Opioids are the most common medications for moderate to severe pain. Unfortunately, they also have addictive properties that have precipitated opioid misuse and the opioid epidemic. In the present study, we examined the effects of acute administration of oxycodone, a μ-opioid receptor (MOR) agonist, on Ca2+ transient activity of medium-sized spiny neurons (MSNs) in freely moving animals. Ca2+ imaging of MSNs in Dopamine D1-Cre mice (expressing Cre predominantly in the direct pathway) or adenosine A2A-Cre mice (expressing Cre predominantly in the indirect pathway) was obtained with the aid of miniaturized microscopes (Miniscopes) and a genetically-encoded Cre-dependent Ca2+ indicator (GCaMP6f). Systemic injections of oxycodone (3 mg/kg) increased locomotor activity yet, paradoxically, reduced concomitantly the number of active MSNs. The frequency of Ca2+ transients was significantly reduced in MSNs from A2A-Cre mice but not in those from D1-Cre mice. For comparative purposes, a separate group of mice was injected with a non-Cre dependent Ca2+ indicator in the cerebral cortex and the effects of the opioid also were tested. In contrast to MSNs, the frequency of Ca2+ transients in cortical pyramidal neurons was significantly increased by oxycodone administration. Additional electrophysiological studies in brain slices confirmed generalized inhibitory effects of oxycodone on MSNs, including membrane hyperpolarization, reduced excitability, and decreased frequency of spontaneous excitatory and inhibitory postsynaptic currents. These results demonstrate a dissociation between locomotion and striatal MSN activity after acute administration of oxycodone.